Humanities for Humans (De Gruyter, 2025)
Building on the conversation series "Humanities for Humans," this volume introduces prominent academics in a manner that breaks down barriers between campuses and the general public. Sharing about their life journeys and using clear language to communicate their thinking on challenging topics of our day like racism, migration, sustainability, violence, and inequality, these authors probe what’s at stake and suggest pathways to viable solutions.